Tax harmonisation: Does the unanimity rule play a role? - Lisa Grazzini; Tanguy VanYpersele (Fondazione Eni Enrico Mattei (FEEM), 1997)
In this paper, we analyse tax harmonisation in the framework of two asymmetric countries, differing with respect to their capital-labour endowments. In the first part, we analyse how national fiscal policies are decided when countries play a non-cooperative game. At the Nash equilibrium, inefficiency arises because of the corresponding misallocation of resources. Some forms of fiscal policy co-ordination are then studied within the institutional framework of the European Community, where such policy reforms are decided by the unanimity rule. We show that, while the imposition of a minimum level of capital taxation cannot pass, there exist some forms of tax convergence that can be accepted.
Keywords: 330; Steuerharmonisierung; Finanzpolitik; Abstimmungsregel; Spieltheorie; Theorie; EU-Staaten